Pengurusan pembangunan harta wakaf: Pengalaman Majlis Agama Islam Negeri Pulau Pinang (MAINPP) terhadap wakaf Setee Aishah - Hashim, Hydzulkifli; Ab. Rahman, Asmak (Universiti Utara Malaysia Press, 2012)
Purpose– The purpose of this study is to review the waqf property development that has been implemented by the Islamic Religious Council of Pulau Pinang (MAINPP) as a trustee for the endowment land named waqf Seetee Aishah. The Seetee Aishah endowment land located at Seberang Jaya, Pulau Pinang. This waqf land was developed into a housing estate. Methodology– This study employs two types of methods – library research and field research. The library research is used as the first method for collecting data, where the data is extracted from fiqh contemporary books,fiqh classic books, journals, internet websites, annual reports and scientific conference papers.The second method of data collection is field research,where interviews were conducted with the head of the endowment (waqf) and also the project manager of the Seetee Aishah endowment at MAINPP. The methods of analysis covered three aspects – deductive, inductive and comparative.Findings – This study finds that the development of waqf properties at Pulau Pinang was carried out by the collaboration between MAINPP with the developer (UDA Holdings Bhd.).Because of the lack of cashflows, MAINPP is not able to provide financial capital (liquid assets) to carry out the development of waqf property, but able to provide unmovable capital(waqf land) for the project.Originality/Value – This study proves that joint venture between MAINPP and UDA Holdings Bhd. in developing the waqf land could increase the value of existing waqf properties.The joint venture implemented by MAINPP can also be used as a model for the other states in Malaysia to construct their waqf property more productive.